Management of pineal region tumors in a pediatric case series - Schulz, Matthias (Neurosurg Rev, 2020)
Pineal region tumors commonly present with non-communicating hydrocephalus. These heterogeneous histological entities require different therapeutic regimens. We evaluated our surgical experience concerning procurance of a histological diagnosis, management of hydrocephalus, and choice of antitumoral treatment. We analyzed the efficacy of neuroendoscopic biopsy and endoscopic third ventriculocisternostomy (ETV) in patients with pineal region tumors between 2006 and 2019 in a single-center retrospective cross-sectional study with regard to diagnostic yield, hydrocephalus treatment, as well as impact on further antitumoral management. Out of 28 identified patients, 23 patients presented with untreated hydrocephalus and 25 without histological diagnosis. One patient underwent open biopsy, and 24 received a neuroendoscopic biopsy with concomitant hydrocephalus treatment if necessary. Eighteen primary ETVs, 2 secondary ETVs, and 2 ventriculoperitoneal shunts (VPSs) were performed. Endoscopic biopsy had a diagnostic yield of 95.8% (23/24) and complication rates of 12.5% (transient) and 4.2% (permanent), respectively. ETV for hydrocephalus management was successful in 89.5% (17/19) with a median follow-up of more than 3 years. Following histological diagnosis, 8 patients (28.6%) underwent primary resection of their tumor. Another 9 patients underwent later-stage resection after either adjuvant treatment (n = 5) or for progressive disease during observation (n = 4). Eventually, 20 patients received adjuvant treatment and 7 were observed after primary management. One patient was lost to follow-up. Heterogeneity of pineal region tumor requires histological confirmation. Primary biopsy of pineal lesions should precede surgical resection since less than a third of patients needed primary surgical resection according to the German pediatric brain tumor protocols. Interdisciplinary decision making upfront any treatment is warranted in order to adequately guide treatment.